Comparative Analysis of Attitudes and Knowledge Using Environmental-Based Learning Methods on Natural Resource Management Material at SMAN 1 Bangkalan - R.Aj. Hafidah; Umsiyah; Inung Sektiyawan; Baiti Nur Saida (Universitas Negeri Surabaya, 2025)
This study aims to determine whether there is a difference between attitude values and knowledge values using the Environmental Based Learning method on the material of natural resource management for class XI Kurmer and to determine the reliability of the assessment instrument. The method used in this study is a comparative method using t-test statistics with parameters of attitude and knowledge values from the test. The trial subjects of the study were 200 class XI students at SMA Negeri 1 Bangkalan. The t-test statistical analysis technique was used to compare the attitude and knowledge values obtained through the application of Environmental Based Learning compared to schools that did not receive treatment. While reliability was analyzed using a qualitative descriptive method. The results of this study are that there is a significant difference between attitude values and knowledge values using the Environmental Based Learning method on the material of Natural Resource Management for class XI and the instrument is declared unreliable in assessing student competencies so that it cannot be applied to help teachers assess the achievement of students' attitude and knowledge competencies based on the Independent CurriculumKeywords: Attitude, Knowledge, Learning